2021
DOI: 10.1111/jgs.17446
|View full text |Cite
|
Sign up to set email alerts
|

From research to bedside: Incorporation of a CGA‐based frailty index among multiple comanagement services

Abstract: The comprehensive geriatric assessment (CGA) is the core tool used by geriatricians across diverse clinical settings to identify vulnerabilities and estimate physiologic reserve in older adults. In this paper, we demonstrate the iterative process at our institution to identify and develop a feasible, acceptable, and sustainable bedside CGA-based frailty index tool (FI-CGA) that not only quantifies and grades frailty but also provides a uniform way to efficiently communicate complex geriatric concepts such as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…We analyzed a cohort of older adults undergoing thoracic surgery who were evaluated and collaboratively managed by a geriatricthoracic team. Frailty, as measured using a rigorous FI-CGA 26 , was prevalent in our cohort (38%). Notably, most of these individuals (82%) had degrees of frailty that often are undetected by nongeriatric teams, which we defined as "occult frailty."…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We analyzed a cohort of older adults undergoing thoracic surgery who were evaluated and collaboratively managed by a geriatricthoracic team. Frailty, as measured using a rigorous FI-CGA 26 , was prevalent in our cohort (38%). Notably, most of these individuals (82%) had degrees of frailty that often are undetected by nongeriatric teams, which we defined as "occult frailty."…”
Section: Discussionmentioning
confidence: 87%
“…We analyzed a cohort of older adults undergoing thoracic surgery who were evaluated and collaboratively managed by a geriatric‐thoracic team. Frailty, as measured using a rigorous FI‐CGA 26 , was prevalent in our cohort (38%). Notably, most of these individuals (82%) had degrees of frailty that often are undetected by nongeriatric teams, which we defined as “occult frailty.” We identified multiple geriatric‐specific interventions incorporated by the multidisciplinary team, and despite the high prevalence of frailty, these patients had similar postoperative outcomes compared to those without frailty with no evidence of higher rates of complications or longer hospital stay.…”
Section: Discussionmentioning
confidence: 87%
“…Despite its importance, assessing and interpreting frailty has long been regarded as a barrier in incorporating this condition into real-world clinical practice (14). However, the Clinical Frailty scale (CFS), a simplified measure including pictographs and brief descriptions on global fitness and functional capabilities, has been suggested as a viable approach (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, health care systems have been faced with an increasing number of older multimorbid patients, requiring continuous structural adjustment. Among other things, this has prompted the emergence of comprehensive geriatric care (CGC), a multidisciplinary intervention strategy developed to satisfy medical care requirements but also focusing on patients’ functional abilities in order to improve and/or maintain their independence [ 1 , 2 , 3 ]. Many investigations have indicated that patients might benefit from this approach [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%